Motivation for Japanese baseball fans' interest in Major League Baseball. (25th July 2005) - Hong, JinBae; McDonald, Mark A.; Yoon, ChunSuk; Fujimoto, Junya
Since Japanese baseball players began playing in Major League Baseball (MLB) in the mid-1990s, the popularity of MLB has been increasing in the Japanese market. This popularity has resulted in increased MLB TV ratings, sales of MLB licensed merchandise and sponsorships, and event business in Japan. This study identified three primary spectator motives for Japanese interest in MLB: overall interest in baseball; interest in players; quality of games. The results of structural equation modelling indicate that these motives predict the Japanese fans' emotional attachment, attitudinal, or behavioural loyalty toward MLB. In addition, emotional attachment predicts attitudinal loyalty, and attitudinal loyalty leads to behavioural loyalty. The results of this study suggest a number of marketing strategies MLB should develop for continuing and enhancing success in foreign markets, including: more presence of local or star players; more games played in foreign markets; grass root marketing; programming with international players and actively communicating with international fans.